Pengaruh Metode Bobath Terhadap Kemampuan Berdiri Dan Berjalan Pada Anak Cerebral Palsy Spastik Diplegia Di Klinik Terapi Terpadu - Maya Aulia; Mustafa Al Haris; Ida Aryani Pasaribu (LPPM STIKES Siti Hajar dan Insight Power, 2023)
Background: Cerebral Palsy (CP) varies greatly from mild to severe depending on the extent of damage in the central nervous system (CNS). This also limits the mobility of the child, Spasticity, posture abnormalities, delays in standing and walking independently and gait disturbances cause lower extremity skeletal deformities. The problem that arises is the abnormality of postural tone which affects the ability to stand and walk, the purpose of this study is to improve the ability to stand and walk in spastic diplegia cerebral palsy children at an integrated therapy clinic. The current training method used is Bobath therapy with a Neuro Development Treatment (NDT) approach using Gross Motor Function Measure (GMFM) as a measuring tool. Sample determination using purposive sampling technique with a total sample of 10 children aged 2-6 years and has met the inclusion and exclusion criteria. The results of the study were analyzed using the Shapiro-Wilk Test data normality test and the Paired T-test test. Results: The correlation test results of the Paired T-test test obtained a value of p = 0.000 (p <0.05) which means that there is an effect of bobath on the ability to stand and walk.Keywords: Cerebral Palsy (CP), Neuro Development Treatment (NDT)